Menganalisis hubungan dan implikasi nilai-nilai karakteristik dalam kompetensi inti - Warih Zunu Pamungkas; Yuliana Dwi Hapsari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The aim of this research is to analyze the relationship and influence of character values ​​on Main Competencies (KI), Main Competencies (KD), Learning Outcomes (CP), Competency Achievement Indicators (GPA) and Learning Objectives in the Islamic context. Religious education . The literature research method with the topic